2016
DOI: 10.1039/c6cp00075d
|View full text |Cite
|
Sign up to set email alerts
|

Glass polymorphism in glycerol–water mixtures: I. A computer simulation study

Abstract: Computer simulations of glassy water–glycerol mixtures: molecular structure and density during the pressure-induced amorphous–amorphous (LDA–HDA) transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 78 publications
3
30
0
Order By: Relevance
“…That is, we interpret these observations in the sense that the sample formed at high pressure by PIA consists of MFCS and HDA, which upon decompression converts to MFCS and LDA, where the LDA contains glycerol molecules, such that the LDA density significantly increases with increasing x. We note that our earlier experiments 224 and MD simulations, 253 as well as available experimental results 230,244,254 confirm that glycerol is soluble both in LDA and HDA. These observations are in striking contrast to LiCl-H 2 O: whereas the difference in step height is slightly overestimated for LiCl-H 2 O (see double headed arrows in Fig.…”
Section: Other Salt Solutionssupporting
confidence: 70%
See 3 more Smart Citations
“…That is, we interpret these observations in the sense that the sample formed at high pressure by PIA consists of MFCS and HDA, which upon decompression converts to MFCS and LDA, where the LDA contains glycerol molecules, such that the LDA density significantly increases with increasing x. We note that our earlier experiments 224 and MD simulations, 253 as well as available experimental results 230,244,254 confirm that glycerol is soluble both in LDA and HDA. These observations are in striking contrast to LiCl-H 2 O: whereas the difference in step height is slightly overestimated for LiCl-H 2 O (see double headed arrows in Fig.…”
Section: Other Salt Solutionssupporting
confidence: 70%
“…This can be explained by considering that (i) there are water molecules in the solution that do not exhibit polyamorphism (see Section 3.1.1), e.g., water molecules located in the interphase (between MFCS and water domains), or (ii) by a smaller density difference between the LDA and HDA water domains within the glycerol-water than in the case of pure water. Our MD simulations show that adding glycerol considerably increases the density of the LDA solution while barely changing the density of the HDA solution, 253 supporting scenario (ii). Scenario (i) seems unlikely, since one would need more water molecules trapped in the interphase than in the MFCS.…”
Section: Other Salt Solutionssupporting
confidence: 70%
See 2 more Smart Citations
“…There are several theoretical and computational studies of the phase behavior of supercooled aqueous solutions. [54][55][56][57][58][59][60][61][62] Paschek calculated the excess chemical potential of Ar in TIP5P-E water using the particle insertion method and found that the solubility of Ar in LDL is much higher than that in HDL. 62 Le and Molinero performed MD simulations of an aqueous solution of hydrophilic particles using a coarse-grained model.…”
Section: Introductionmentioning
confidence: 99%